REGULATIONS AND RULES OF INTERNATIONAL SPORT ORGANIZATIONS - Muhammadiyeva Nodira Xudoyor qizi; Baxodirov Aziz Baxodir o‘g‘li (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article explores the system of regulations and rules that govern international sport organizations. As global sports continue to expand in scale and influence, the need for transparent, standardized, and enforceable regulations becomes essential. The research focuses on how organizations such as the International Olympic Committee (IOC), Fédération Internationale de Football Association (FIFA), and World Anti-Doping Agency (WADA) establish, implement, and monitor their regulatory frameworks. It also examines issues of ethics, fair play, and compliance. The findings demonstrate that well-designed rules ensure equality, integrity, and discipline in international sports, strengthening both athletes’ trust and the credibility of global sport institutions.